Evaluation of Project “Enhancing Quality of Work Life and Health Promotion Capacity of Government Organization during Changing into Healthy Organization” - kraivixien, Dhitiporn; Khaikleng, Piyapong; Sakuntanak, Panida; Srikleub, Kanit (Journal of Humanities and Social Sciences Thonburi University, 2022)
This study was a summative evaluation research using the qualitative data from Project “Enhancing quality of work life and health promotion capacity of government organization during changing into health organization” which had 3 objectives: (1) to evaluate the results and the fulfillments of the project KPIs (2) to evaluate the healthy organization policy-deliverology process; and (3) to provide improvement recommendations for future projects. The results from the project strategic perspective be evaluated as Good were 46.15%, while the results from outputs and outcomes perspectives fulfilled the KPIs at 88.88% and 100%, respectively. As for the policy-deliverology the results with respect to the no returning to the original stage was lower than the results from the building basic deliverology process, the problem understanding process, and deliverology planning process, respectively. The recommendations were offered in 4 areas: project operation and management; the project’s healthy organization deliverology; delivering healthy organization concepts to government organizations; and healthy organization innovations.